Analisis Performa Chatbot Berdasarkan 20 Fitur Pada Parameter Industri Perbankan di Indonesia - Asmara, Gregorius Peitra Dirgantara Sakti Nikula; Afifah, Vivi; Artheswara, Lana Ciarna (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
The development of the banking industry in Indonesia continues to spur digital acceleration andinnovation in order to provide the best service for customers. In today's world, almost all banks in Indonesiahave implemented chatbot innovation as a digital banking service medium based on Artificial Intelligence(AI) which has various functions for customers. However, it is suspected that the use of this chatbot hasseveral obstacles, especially in offering features in the data chatbot itself. In this research, chatbotperformance will be analyzed and identified based on standard banking industry parameters related tochatbots which contain 20 features to measure chatbot performance. The samples for this research are fourchatbots from the four largest banks in Indonesia whose identities are kept secret. The results of this researchshow that chatbot C has the highest level of performance at 77.5%. Meanwhile, chatbots A and D have aperformance of 45%, followed by chatbot B with a performance value of 35%. These results show that theperformance of chatbots in the banking industry in Indonesia is still not optimal and there are stillrecommendations for improvements in terms of chatbot features to create a good customer experience forcustomers.